109k views
5 votes
Factor out the coefficient of the variable term.
The expression 1.5y – 6 factored is

1 Answer

3 votes

Answer:y=4

Step-by-step explanation: Simplifying

1.5y + -6 = 0

Reorder the terms:

-6 + 1.5y = 0

Solving

-6 + 1.5y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.

-6 + 6 + 1.5y = 0 + 6

Combine like terms: -6 + 6 = 0

0 + 1.5y = 0 + 6

1.5y = 0 + 6

Combine like terms: 0 + 6 = 6

1.5y = 6

Divide each side by '1.5'.

y = 4

Simplifying

y = 4

User Whizzle
by
7.8k points